If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -79 + -12x = -4x + 89 Reorder the terms: -79 + -12x = 89 + -4x Solving -79 + -12x = 89 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -79 + -12x + 4x = 89 + -4x + 4x Combine like terms: -12x + 4x = -8x -79 + -8x = 89 + -4x + 4x Combine like terms: -4x + 4x = 0 -79 + -8x = 89 + 0 -79 + -8x = 89 Add '79' to each side of the equation. -79 + 79 + -8x = 89 + 79 Combine like terms: -79 + 79 = 0 0 + -8x = 89 + 79 -8x = 89 + 79 Combine like terms: 89 + 79 = 168 -8x = 168 Divide each side by '-8'. x = -21 Simplifying x = -21
| -54=16+y | | 2x+6=20+x | | 4x-9=3x+14 | | 0.5x+7=0.75-4 | | -54=15+y | | -26+7x=10x+10 | | [t+9]-8=5 | | 8x+4-2=-5+4x | | x^2+12=-8x | | Y=30+0.85Y+20+40 | | 4/6=238/x | | x+15=-21 | | 5x-52=11x+44 | | 22/16x+50=128 | | -3x-4=8x+7 | | 1/5x-9=-9 | | v=2nr | | 3x+7x-2=6 | | 70+25w=200 | | 1/2y-2/3=7/8 | | 1-4b+2-5b= | | 125=50+.50b | | 12(4/(1/3))=x | | 12m=276 | | 15-7x=18-6x | | x/2+1/4+3/4 | | x=.4+.2y | | 12*(4/1/3)=x | | -0.09m+-22m= | | 6(1-2/3x)=42 | | -(3p-15)=6(2p+5) | | 4/1/3=12/x |